A randomised study for optimising crossover from ticagrelor to clopidogrel in patients with acute coronary syndrome - Pourdjabbar, Ali; Hibbert, Benjamin; Chong, Aun-Yeong; Le May, Michel R.; Labinaz, Marino; Simard, Trevor; Ramirez, F. Daniel; Lugomirski, Peter; Maze, Ronnen; Froeschl, Michael; Glover, Christopher; Dick, Alexander; Marquis, Jean-Francois; Bernick, Jordan; Wells, George; So, Derek Y. F.; the CAPITAL Investigators; on behalf of (Thrombosis and Haemostasis, 2017)
Ticagrelor has been endorsed by guidelines as the P2Y12 inhibitor of choice in patients with acute coronary syndrome. Clinically, some patients on ticagrelor will require a switch to clopidogrel; however, the optimal strategy and pharmacodynamics effects of switching remain unknown. Patients with an indication to switch were randomly assigned to either a bolus arm (Clopidogrel 600 mg bolus followed by 75 mg daily, n=30) or a no-bolus arm (Clopidogrel 75 mg daily, n=30). Blood samples were collected at baseline, 12, 24, 48, 54, 60 and 72 hours (h) for assessment of platelet reactivity. The primary outcome was P2Y12 reactivity units (PRU) at 72 h. Secondary outcomes included: PRUs at each time point, incidence of high on-treatment platelet reactivity (HPR), major adverse cardiac events (MACE) and TIMI bleeding at 30 days. Serial PRUs increased after switching to clopidogrel in both groups. At 72 h, no difference in PRU was observed (165.8 ± 71.0 vs 184.1 ± 67.7, bolus vs no bolus, respectively, p=0.19). At 48 h the PRUs were significantly lower in the bolus arm (114 ± 73.1 vs 165.1 ± 70.5, respectively; p=0.0076) and at 72 h, there was a significant reduction in incidence of HPR (26.7 % vs 56.7 %, p=0.02). No differences in MACE or TIMI bleeding were observed. Although a bolus strategy was not associated with improved platelet inhibition at 72 h; at 48 h, platelet inhibition was superior with reduced incidence of HPR. Larger studies will be required to determine its clinical significance. Until then, decision for giving a bolus of clopidogrel at the time of a switch may in part be dependent on the indication for switching, especially if there are concerns for bleeding risk.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Pharmacodynamics; acute coronary syndrome; platelet function; ticagrelor; clopidogrel